Acceptance, fatigue severity and self-reported physical activity in individuals with chronic fatigue syndrome/myalgic encephalomyelitis. Issue 2 (3rd April 2019) - Chapman, Neil; Broadbent, Suzanne; Coutts, Rosanne
ABSTRACT: Background: Acceptance is a coping strategy associated with chronic pain management, but its effectiveness is unclear for Chronic Fatigue Syndrome/Myalgic Encephalomyelitis (CFS/ME). Objective: The aim of the study was to investigate the relationship between acceptance, fatigue severity, pain and self-reported physical activity in individuals with CFS/ME. Method: Ten females and seven males diagnosed with CFS/ME (51.9 ± 8.8 years), and gender, age-matched sedentary controls, completed self-reported measures of acceptance, fatigue severity and physical activity. Acceptance was measured using the Chronic Pain Acceptance Questionnaire and Acceptance and Action Questionnaire-II. Fatigue was assessed with the Fatigue Severity Scale, and Physical Activity using the International Physical Activity Questionnaire – Short Form. Self-reported physical activity was calculated using categorical and continuous measures (MET-minutes). Result: CFS/ME and control groups were compared using Independent t -tests and Spearman's Rho correlations. The CFS/ME group reported significantly greater fatigue severity and psychological inflexibility, and lower pain willingness and time spent sitting than controls. However, no between-group differences for activity engagement or physical activity. The CFS/ME group showed a negative relationship between pain willingness and psychological inflexibility, and a positive relationship between walking time and the time since symptom onset, and time since diagnosis. Conclusion: Despite reporting greater fatigue and less acceptance of their illness, CFS/ME patients had comparable levels of physical activity to controls, possibly due to pacing their activity to avoid symptom exacerbation. CFS/ME patients with an older diagnosis walked further than the newly diagnosed, suggesting the development of better coping skills and management strategies over time.